Pengaruh Pembelajaran Etnopedagogi untuk Aksara Jawa Berbasis Metode Montessori terhadap Karakter Kecerdasan Sosial Siswa Sekolah Dasar - Gregorius Ari Nugrahanta; Eko Hari Parmadi; Fransiska Tjandrasih Adji; Hilary Relita Vertikasari Sekarningrum (Jurnal Studi Guru dan Pembelajaran, 2024)
Concern about the low level of social intelligence among elementary school students is something that needs to be addressed immediately. Efforts to foster social intelligence at SD Kanisius Sorowajan Yogyakarta are still carried out through habituation activities at school that are not carried out every day. However, SD Kanisius Sorowajan has not implemented efforts to improve the character of social intelligence by integrating learning in the classroom using innovative learning methods and adapted to local culture. The purpose of this study was to determine the effect of ethnopedagogical learning for Javanese script using the Montessori method on the social intelligence character of elementary school students. For this reason, one group pretest-posttest design was used as the research method. A total of 20 children of class IVA at SD Kanisius Sorowajan, Yogyakarta, were involved as subjects in this study. The research instrument used in this study was a multiple-choice test instrument with 10 questions according to the indicators of social intelligence. The data obtained were then analysed using the IBM Statistics version 26 for windows program to calculate the effect and effectiveness with a 95% confidence level and with a two-tailed test. The research findings showed that ethnopedagogical learning for Javanese characters using the Montessori method had an effect on children's social intelligence characters (p < 0.05). The effect size was categorised as large (r = 0.8896 or equivalent to 79.14%). The learning effectiveness level is included in the high effectiveness level (N-gain score 82.52%). The results of semantic analysis show a dynamic pattern of social intelligence characters that can be classified into three dimensions, namely 1) moral knowledge, which is expressed by indicators of skill evaluation, social relationships, understanding expressions, managing emotions, 2) moral feelings, which are expressed by indicators of empathy, emotional turmoil, understanding feelings, assessing motivation, and 3) moral action, which is indicated by indicators of building relationships and good cooperation.